Understanding the Effect of Social Media Marketing on Purchase Intention : a Value-based Adoption Model - Vidyanata, Deandra (JDM (Jurnal Dinamika Manajemen), 2022)
The rapid use of social media has skyrocketed over the past decade all over the world, including in Indonesia. Organizations can significantly benefit by utilizing social media as an integral part of their marketing strategy. However, there is no consensus regarding to which extent Social Media Marketing (SMM) is able to influence Purchase Intention (PI). The purpose of this study is to examine the effect of SMM on PI based on the Value-Based Adoption Model (VAM). The research population of this study is 791 thousand accounts of @halodoc Instagram followers. Halodoc becomes an interesting object to study because it is engaged in the healthcare sector, where consumers will be thoroughly evaluating the Perceived Value (PV) of the service offered. The sample consists of 130 respondents using the purposive sampling method. This study concludes that SMM has no direct influence on PI; SMM has a positive and significant effect on PV; PV has a positive and significant effect on PI and PV fully mediates the influence between SMM on PI. This study confirms that the SMM should be focusing on establishing consumers’ favorable internal response. Nevertheless, this research still has some technical limitations, where the prospective respondents were reluctant to reply direct messages from unknown senders. .